2011
DOI: 10.4161/rna.8.6.16691
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of PKA-controlled CaMKK2 variants on neuronal differentiation

Abstract: Regulation between protein kinases is critical for the establishment of signaling pathways/networks to 'orchestrate' cellular processes. Besides posttranslational phosphorylation, alternative pre-mRNA splicing is another way to control kinase properties, but splicing regulation between two kinases and the effect of resulting variants on cells has barely been explored. Here we examined the effect of the protein kinase A (PKA) pathway on the alternative splicing and variant properties of the Ca²⁺/calmodulin-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 60 publications
2
32
0
1
Order By: Relevance
“…One study also showed the enzyme encoded by CAMKK2 can phosphorylate AMP-activated protein kinase. 68 The CAMKK2 gene has the strongest expression in brain 31 and it influences signaling cascades that are involved with learning and memory, 32,69 neuronal differentiation and migration, 70 neurite outgrowth 34,35,70 and synapse formation.…”
Section: Resultsmentioning
confidence: 99%
“…One study also showed the enzyme encoded by CAMKK2 can phosphorylate AMP-activated protein kinase. 68 The CAMKK2 gene has the strongest expression in brain 31 and it influences signaling cascades that are involved with learning and memory, 32,69 neuronal differentiation and migration, 70 neurite outgrowth 34,35,70 and synapse formation.…”
Section: Resultsmentioning
confidence: 99%
“…Two major transcripts are generated by use of polyadenylation sites present in the last two exons. Additionally, CaMKK2 transcripts can be generated by alternative splicing of internal exons 14 and/or 16; this mechanism produces variants with different roles in neuronal differentiation (16,17). PKA and CaMKIV have been reported to be involved in regulation of alternative splicing of the CaMKK2 transcript (17).…”
Section: Camkk2: Structure and Functionmentioning
confidence: 99%
“…CaMKK and CaMKI co-localize with ␤PIX (p21-activated kinase-interacting exchange factor) and GIT1 (G-protein-coupled receptor kinase-interacting protein 1) in dendritic spines as part of a multiprotein complex that regulates actin dynamics (43). Differential splicing and phosphorylation of critical Ser residues affect the ability of CaMKK2 to control dendrite/axon formation (17,27). Thus, a CaMKK2/CaMKI cascade regulates learning-induced neuronal cytoskeleton remodeling associated with memory formation.…”
Section: Camkk2 and Brain Functionsmentioning
confidence: 99%
See 2 more Smart Citations